STABILITY INDICATING CHIRAL HPLC METHOD FOR THE ESTIMATION OF PIOGLITAZONE ENANTIOMERS IN PHARMACEUTICAL FORMULATION - B, GOWRAMMA; SN, MEYYANATHAN; B, BABU; KRISHNAVENIN,; KUMAR KR, SENTHIL (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: A stability indicating chiral high performance liquid chromatographic (HPLC) method was developed and validated for the separated (S) and (R) pioglitazone in raw material and its determination in the presence of degradation products formed during forced degradation studies. Methods: In the present study, an isocratic normal phase-HPLC method was developed with stationary phase as ACI Cellu 1 (150 mm × 4.6 mm i.d., 5 μ) column and n-hexane: N-propyl alcohol (80:20, V/V) as mobile phase. The entire study was performed using 1.0 ml/minute as flow rate and the detection wavelength at 233 nm. The pioglitazone (R and S) was exposed to various stress condition such as hydrolytic (acid and base), neutral, oxidative, and photolytic. The stressed samples were analyzed by the proposed method. Result: The described method was linear over the range of 5-15 µg/ml for R-pioglitazone and 4-14 µg/ml for S-pioglitazone. The limit of detection and limit of quantification of S-pioglitazone and R-pioglitazone were found to be 1.4 μg/ml and 4.26 μg/ml, respectively. The recovery study of S and R-Pioglitazone from tablets formulation ranged from 97.14% to 100.04%, respectively. Conclusion: The developed method can be applied in the quality control of drug products. Keywords: Stability-indicating method, Validation, Chiral, Pioglitazone.